Quantification of terrestrial laser scanner (TLS) elevation accuracy in oil palm plantation for IFSAR improvement - Muhadi , N. A.; Abdullah, Ahmad Fikri; Mohd Kassim, Muhamad Saufi (IOP Publishing, 2016)
In order to ensure the oil palm productivity is high, plantation site should be chosen wisely. Slope is one of the essential factors that need to be taken into consideration when doing a site selection. High quality of plantation area map with elevation information is needed for decision-making especially when dealing with hilly and steep area. Therefore, accurate digital elevation models (DEMs) are required. This research aims to increase the accuracy of Interferometric Synthetic Aperture Radar (IFSAR) by integrating Terrestrial Laser Scanner (TLS) to generate DEMs. However, the focus of this paper is to evaluate the z-value accuracy of TLS data and Real-Time Kinematic GPS (RTK-GPS) as a reference. Besides, this paper studied the importance of filtering process in developing an accurate DEMs. From this study, it has been concluded that the differences of z-values between TLS and IFSAR were small if the points were located on route and when TLS data has been filtered. This paper also concludes that laser scanner (TLS) should be set up on the route to reduce elevation error.